MacIntyre, Weber and institutional logics - Chu, Irene (Frontiers in Sociology, 2022)
This paper explores ‘what more and what else’ MacIntyre’s concepts can contribute, specifically as applied to neoinstitutional theory and especially institutional logics. Drawing on the common influence of Max Weber’s work as further developed by Friedland, MacIntyre’s concept of eudaimonia being furthered by the pursuit of internal goods supported by external goods is used to develop a typology of goods. This typology is then deployed to show how the differing institutional logics of, for example, the market and the family have differing rationalities with differing emphases on internal and external goods, and consequently differing moral content. A simple picture of the market economy is then developed to show how such MacIntyrean concepts can be used to address the critique of a lack of morality in neoinstitutional theory. Conversely, the analytical framework provided by the institutional logics perspective is used to show how MacIntyrean concepts can be applied practically in a way that provides an interesting perspective on the current world.